2005
DOI: 10.1007/s11199-005-7733-4
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Peer Sexual Harassment in Swedish High Schools: What Factor Structures Show the Best Fit to Girls' and Boys' Self-Reports?

Abstract: Dimensions of peer sexual harassment in schools were analyzed with confirmatory factor analyses of data from a questionnaire study of 980 Swedish high-school students. The factorial structures suggested in the literature on sexual harassment in the workplace showed a bad fit to the student data, especially for boys. A nested structure, with one general factor and two specific factors (closest to the hostile environment and sexual attention categories), appeared to offer the best fit-to-data for female students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
2
26
1
1
Order By: Relevance
“…McMaster et al ( 2002 ) suggest a three factor solution (verbal, physical, and visual) while Vega-Gea et al ( 2016 ) suggest a two dimensional solution (verbal–visual and physical). Witkowska and Kjellberg ( 2005 ) propose a nested structure with a general sexual harassment factor and two specific factors (hostile environment and sexual attention) for female but not for male students for whom only a general sexual harassment factor had an acceptable fit. As these authors have not used the exact same items that are being used in the current study, we conducted an Exploratory Factor Analysis within Mplus using quatermin and varimax rotation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…McMaster et al ( 2002 ) suggest a three factor solution (verbal, physical, and visual) while Vega-Gea et al ( 2016 ) suggest a two dimensional solution (verbal–visual and physical). Witkowska and Kjellberg ( 2005 ) propose a nested structure with a general sexual harassment factor and two specific factors (hostile environment and sexual attention) for female but not for male students for whom only a general sexual harassment factor had an acceptable fit. As these authors have not used the exact same items that are being used in the current study, we conducted an Exploratory Factor Analysis within Mplus using quatermin and varimax rotation.…”
Section: Methodsmentioning
confidence: 99%
“…We argue that understanding how sexual harassment is used as a tool to establish asymmetric power between boys and girls, as well as between boys, may assist in interpreting directional associations between sexual harassment victimization and depressive symptoms. Furthermore, sexual harassment may take physical, verbal or visual forms (AAUW 2001 ), but, depending on items used to measure sexual harassment, other dimensions (e.g., hostile environment) have been proposed in adolescent populations (Vega-Gea et al 2016 ; McMaster et al 2002 ; Witkowska and Kjellberg 2005 ). In order to inform future preventive measures, investigating the directional pathways of dimensions of sexual harassment and depressive symptoms in this age group makes it possible to obtain information about what behaviors in more detail that are associated with what dimensions of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the disparity in the data lends itself to controversy and highlights the gap in the research regarding the means of measuring this phenomenon, it is that some studies use a single item to measure peer sexual harassment and others use large scales. Theoretical models have been quite influential insofar as considering the phenomenon a one-dimensional ( Menesini and Nocentini, 2008 , Schnoll et al, 2015 ), two-dimensional ( Ortega et al, 2010 , Witkowska and Kjellberg, 2005 ), or three-dimensional construct ( Ormerod, Collinsworth, & Perry, 2008 ). It is important to take account of this consideration given that one-dimensional measures tend to considerably increase prevalence rates.…”
mentioning
confidence: 99%
“…However, the variability in these dimensions has not been accompanied by conclusive studies that have explored the factorial structure of the construct based on Confirmatory Factor Analyses. For example, the three-dimensional model proposed by Fitzgerald and colleagues ( Fitzgerald, Gelfand, & Drasgow, 1995 ) has received moderate support, with some studies having confirmed its structure, whereas in other studies the data do not fit the model, with the best-fit models being the two-dimensional type ( Espelage et al, 2012 , McMaster et al, 2002 , Ortega et al, 2010 , Wei and Chen, 2012 , Witkowska and Kjellberg, 2005 ). What has proven conclusive is the need to differentiate between boys and girls, given that studies have found the experience, interpretation and expression of this phenomenon to be different depending on the gender ( Witkowska & Kjellberg, 2005 ).…”
mentioning
confidence: 99%
“…UU. o Canadá revelan una incidencia alta de victimización; el 83% de las estudiantes universitarias estadounidenses según la Asociación Americana de Mujeres Universitarias (AAUW, 2011; Hill y Kearl, 2011) y el 77% de las chicas suecas encuestadas habían sufrido acoso sexual (Witkowska y Kjellberg, 2005). Además, el 87% decían que habían padecido secuelas y efectos negativos estresantes tras ser acosadas (AAUW, 2011;Graham et al, 2017).…”
Section: Introducción Estado De La Cuestión Y Objetivosunclassified